The Application of Slow Deep Breathing and Spiritual Emotional Freedom Technique in a Patient with Rectal Cancer Experiencing Chronic Pain and Anxiety: A Case Report - Rani Ahdalita; Titis Kurniawan; Tuti Pahria (Universitas Malahayati Lampung, 2026)
ABSTRACT Rectal cancer is a malignancy of the lower gastrointestinal tract that is often accompanied by chronic pain and anxiety, particularly in patients undergoing chemotherapy. These conditions affect physical, psychological, and spiritual aspects, thus requiring a holistic nursing care approach. This case report aimed to describe the patient’s response to a combination of Slow Deep Breathing (SDB) and Spiritual Emotional Freedom Technique (SEFT) interventions in reducing pain and anxiety. This study employed a case report design involving a 48-year-old male patient diagnosed with stage III rectal cancer, accompanied by anemia, who was undergoing chemotherapy. The intervention was administered once daily for three consecutive days, with each session lasting 20–25 minutes. Pain intensity was measured using the Visual Analogue Scale (VAS), while anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HAM-A) before and after the intervention. The results showed a reduction in the pain score from 8 to 5 and a decrease in the anxiety score from 28 to 19. Clinically, the patient appeared more relaxed, cooperative, and showed improved acceptance of his illness. The combination of SDB and SEFT has the potential to serve as a complementary nursing intervention that supports a holistic approach in the care of patients with rectal cancer. Keywords: Rectal Cancer, Slow Deep Breathing, Spiritual Emotional Freedom Technique, Pain, Anxiety.